Development issues of a new SRC "Baiterek" - Мұстафинов, Е; Рамазанова, Ж (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The creation of a space rocket complex in the Republic of Kazakhstan will allow to implement international projects, attract foreign investment, create jobs in the Baikonur cosmodrome, high-tech jobs for residents of Baikonur and improve each sector of Kazakhstan by providing space launch services, enter the commercial space market allows. At the same time, great importance is attached to the environmental component. The project is a joint project of the Republic of Kazakhstan and the Russian Federation.